Enhancing English Reading Comprehension of Thai Secondary School Students through the Integration of Technology into Task-based Language Teaching - Srichote, Patipat; Worathumrong, Sakulrat; Yimwilai, Supaporn (Ratchaphruek Journal, 2023)
This research aimed (1) to investigate the effects of the integration of technology into Task-based language teaching (TBLT) on English reading comprehension of English-Chinese program students, (2) to investigate the effects of the integration of technology into TBLT on English reading comprehension of English-Computer program students, (3) to compare the effects of the integration of technology into TBLT on reading comprehension of Thai secondary school students in the English-Chinese program and the English-Computer program. The participants were 56 twelfth-grade students. They were divided into two experimental groups of English-Chinese program and the English-Computer program equally. The instruments in this study included lesson plans and an English reading comprehension test. Mean scores, standard deviations, t-test analysis, and the analysis of covariance were used to analyze the data. The results revealed that there were statistically significant differences in the pre-test and post-test mean scores of the students in both groups at the .05 level. Moreover, the effects of the integration of technology into TBLT on students in both groups had no statistically significant differences. This suggested that the integration of technology into TBLT had positive effects on students who had different English backgrounds.